Complication of Brain Disease During a Radiological Intervention-an Alleged Case of Medical Negligence (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
Infections are the most common predisposing factor both in neonates and children, followed by hematological states, dehydration and various other conditions. Cerebral sino-venous thrombosis (CSVT) encompasses a spectrum of disorders involving thrombosis of the cerebral venous system. Timely diagnosis and treatment are critically important for optimizing outcome. Twenty three months old male child with complaints of vomiting and abnormal eye movements (more on left side) was admitted in a hospital. To rule out intracranial pathology for asymmetrical movements, the child was advised Contrast MRI of Brain. At 08:00 pm, he was given Inj. Gadodiamide (Omniscan) 0.5 mmol/ ml solution for contrast imaging. The child developed sudden cardiac arrest immediately after MRI scan was completed, at 08:50 pm and declared as dead at 09:40 pm. MR Venogram showed thrombus in superior sagittal sinus, proximal part of transverse sinuses & part of straight sinus. Non-Visualization of cerebral cortical veins on both sides was suggestive of thrombosis. Autopsy was performed by board of doctors after a complaint of medical negligence was made by the parents of the deceased. After perusal of clinical record, post-mortem report and FSL report, the board was of the considered opinion that findings were suggestive of thrombus in superior sagittal sinus and proximal part of transverse sinus and in cortical veins of both cerebral hemispheres and was a sudden natural death.
Keywords: Thrombosis; MRI; Medical Negligence; Autopsy